Understand the Role Whistleblowing System and Internal Audit on Fraud Prevention - Agus Bagianto; Hendriyana Hendriyana (Program Studi Akuntansi Universitas Langlangbuana Bandung, 2021)
The development of the business world, especially banking is increasingly complex with a lot of competition. This can trigger the emergence of asset abuse and other fraud. This condition requires managers in the company to always carry out supervision in order to anticipate losses experienced by the company by doing various ways that can prevent them. This study aims to analyze the role of the whistleblowing system and internal audit on the fraud prevention of PT. Bank Mandiri Bandung branch. The factors tested in this study are the whistleblowing system and internal audit as independent variables, while fraud prevention is the dependent variable. The research design used in this study is explanatory. The population in this study were 50 employees of PT. Bank Mandiri Bandung branch. The sampling technique used in this study is to use a saturated sample because the population size is known with certainty. While the analytical method used in this study is multiple linear regression analysis at a significance level of 5%. The program used in analyzing and using the Statistical Package for Social Science (SPSS) Ver. 23. The results of hypothesis testing indicate that the whistleblowing system and internal audit can prevent fraud.